TINJAUAN TENTANG PENERAPAN BERKELANJUTAN LIMBAH KULIT KACANG POHON - Cheryl Wendelin, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Greenhouse gas emissions and water pollution are major causes of food waste, leading to environmental deterioration. Agricultural food waste is one of the significant contributors to environmental degradation. Hence, this review aims to study the utilization of agricultural waste, specifically nutshell waste from various types of tree nuts. A comprehensive literature research was conducted using Science Direct, Wiley Online Library, Springer, and Taylor and Francis. The search strategy involved keywords related to nut shell waste, tree nuts, and utilization. Studies published between 2013 and 2023 were covered and screened using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) approach. A total of 21 studies exploring the utilization of tree nut shell waste were discovered. Findings revealed that tree nut shell waste can serve as adsorbents in the environmental remediation and water treatment sector. Cashew, walnut, and almond nut shells were found to be the most widely utilized due to their availability and favorable properties. However, limitations such as the large sample size and potential publication bias should be acknowledged. This review recommends further development of technologies for converting nut shells, and encourages industries to invest in these technologies to maximize the utilization of tree nut shell waste